An observation of common physiological parameters during esports activity - Koshy, A.; Cironis, L.; McVey, M.; Sousa, A.; Ahmad, S. L.; Hassan, T.; Yuen, K.; Douris, P. C.; Zwibel, H.; DiFrancisco-Donoghue, J. (International Journal of Esports, 2021)
Esports has become a significant international industry with more than 800 million people playing games from various esports titles every month. Physiological stress markers that are commonly utilised in other activities have not been adequately studied in esports. The current study examined changes in such stress markers during competitive gaming, at a cohort and team level. We also explore individual differences in respiration through the use of the Hexoskin suit. Increases in heart rate, respiratory rate and minute ventilation were found in all participants during an esports session when compared with a rest period. Notably, mean heart rate, respiratory rate, and minute ventilation were significantly higher in the winning team as opposed to the losing team (p<0.005). A high level of variance was also observed in between players across teams with respect to the respiratory rate. These results suggest significant cognitive workload and stress placed on players during competitive activity. With greater physiological understanding of the response to cognitive stress and teamwork during gaming, adaptations to training is likely lead to improvements in cognitive health, as well as individual and team performance. Highlights: •Physiological monitoring during esports activity is feasible if a careful protocol is followed •Common physiological parameters such as heart rate, respiratory rate and minute ventilation can vary significantly from restto esports activity •In this study, the winning team in League of Legends had larger increases in physiological parameters from baseline •There appears to be a high level of physiological variance between players during play regardless of the gameoutcome